Interferon Gamma of Multidrug-resistant Tuberculosis (MDR-TB) Patients in Dr. Moewardi Hospital in Surakarta - Hanif Hary Setyawan; . Hudiyono; . Marwoto; Afiono Agung Prasetyo (Nexus Biomedika, 2015)
Background: Interferon-? (IFN-?) produced by CD4+(Th1) T cells plays a critical role in immunityto tuberculosis infection. MDR-TB patients have decreased T cell IFN-?production capacity. Data of IFN-? plasma level of MDR-TB patients in Indonesia, include its association with age and gender, are not yet known. This study was aimed to identify the profile of IFN-? on plasma of MDR-TB patients in Dr. Moewardi Hospital in Surakarta and its association with age and gender. Methods: Blood samples and medical records data from 43 MDR-TB patients in Dr. Moewardi Hospital in Surakarta were collected. Enzyme-linked immunosorbent assay (ELISA) serological test was done to measure IFN-?titer. Results: Twenty samples (46.5%, 20/43) had elevated IFN-? level in their plasma. Elevated IFN-? level was more likely to be found in women (OR 3.63; 95% CI 1.02-12.94) and respondentsaged 21-30 years (OR 4.5; 95% CI 0.79-25.57). No association between elevation of IFN-? level with age (p = 0.450) and gender (p = 0.067). Conclusions: Elevated IFN-? level was found in 46.5% of MDR-TB patients in Dr. Moewardi Hospital in Surakarta.Elevated IFN-? level was more likely to be found in women and respondents aged 21-30 years. Keywords: IFN-g, MDR-TB, Surakarta